Retrospective analysis of patients submitted to surgical treatment of perianal fistula in Santa Marcelina Hospital, São Paulo - Corrêa Neto,Isaac José Felippe (2017)
Abstract Introduction Perianal fistula is a condition commonly found in surgical practice, with an incidence of approximately 1 in 10,000 individuals, with a predisposition for the male gender, occurring mainly in patients between 30 and 50 years and in 80% of the cases originating from infection in the glandular crypts (cryptoglandular). Objective To perform a retrospective analysis using electronic medical record data of patients submitted to surgical treatment for perianal fistula in Santa Marcelina Hospital in São Paulo, as well as to verify the incidence of relapse and anal continence disorders, in addition to the complexity and types of fistulas and patient characterization. Results Two hundred patients were submitted to surgical treatment of perianal fistula were analyzed. Among men, there was a higher incidence of patients with lower educational level (p = 0.02), hypertension (0.03), diabetes (0.05), older age (p = 0.001), whereas among women previous perianal abscess predominated (0.001). There was no statistical difference in anal continence between patients submitted to fistulotomy with or without seton. Conclusion We observed a predominance of male patients and a low incidence of recurrence and symptoms of anal continence disorders, in addition to a predominance of complex fistulas.